MEANING CONSTRUCTION OF STUNTING IN PREGNANT AND BREASTFEEDING WOMEN IN SUKA MAJU VILLAGE TANJUNG TIRAM BATU BARA - Rizki Nanda Saputri; Nurman Achmad; Harmona Daulay (International Journal Of Health Science, 2022)
Stunting is a problem in child growth that is caused by malnutrition over a long period of time. Malnutrition can begin when the child is still in the womb. Stunting can cause a child's body to become stunted or short, the child's intelligence is low, so that the child is susceptible to disease. The stunting prevalence rate in Indonesia was 27.67% in 2019, with a percentage of 30.38% coming from North Sumatra. The causes of stunting are a lack of nutritional support and the presence of infectious diseases in children. In addition, knowledge of nutrition and knowledge of stunting also has an indirect impact on stunting. The phenomenon seen in Suka Maju Village, Tanjung Tiram District is that pregnant women and breastfeeding mothers do not know stunting well, some of them have never even heard of the term stunting, and some others know that stunting is a malnourished child but do not understand what causes it and the impact of children suffering from stunting. With this knowledge, there are no preventive activities carried out by pregnant women and nursing mothers in Suka Maju Village, including the parenting style they apply. Parenting practices that do not support stunting prevention are pregnant women who do not consume highly nutritious foods, provide complementary foods that are not varied, and do not cultivate exclusive breastfeeding.